Réponses

2014-10-04T12:59:53+02:00
C= 2X x 3X + 2X x 7 -5 x 3X -5 x 7 -2 + 2X x X + 2X x -3 -5 x X -5 x -3
= 6X2 + 14X -30 -2 + 2X2 -6X -5X + 15
= 3X2 x 2X2 + 14X -30 -2 + 2X2 -6X -5X + 15
= 2X2 ( 5X2 + 3X -17 )
Meilleure réponse !
2014-10-04T13:52:04+02:00
C= (2x -5)(3x +7) -2 (2x -5)(x -3)
C= 
2x x 3x + 2x x 7 - 5 x 3x - 5 x 7 - 2 + 2x x x -2x x 3 - 5 x x + 5 x 3
C= 
6x² + 14x - 15x - 35 -2 +2x² - 6x - 5x +15
C= 8x² - 12x - 22

D= (2y +9)(1 +2y) 
-4 (1 +2y)²
D= (2y +9)(1 +2y) -4 (1+2y)(1+2y)
D= (1+2y) [ (2y+9) -4  (1+2y)]
D= (1+2y) (2y + 9 -4 x 1 - 4 x 2y)
D= (1+2y) (2y + 9 -4 -8y)
D= (1+2y) (-6y +5)
D= 1 x (-6y) + 1 x 5 - 2y x 6 + 2y x 5
D= -6y + 5 -12y + 10y
D= -8y + 5